2010
DOI: 10.1007/s12105-010-0171-9
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Squamous Cell Carcinomas in HIV-Positive Patients: A Preliminary Investigation of Viral Associations

Abstract: Oncogenic human papillomaviruses (HPVs) are associated with oropharyngeal squamous cell carcinoma (SCC). Infection with human immunodeficiency virus (HIV) increases susceptibility to opportunistic infections and viral-promoted cancers. The prevalences of HPV, herpes simplex virus (HSV), Epstein-Barr virus (EBV), and human herpesvirus-8 (HHV-8) have not been established for head and neck squamous cell carcinoma in HIV-positive patients (HIV+ HNSCC). We have observed that HIV+ HNSCC tend to contain numerous mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 57 publications
4
51
1
Order By: Relevance
“…In the United States, a study was conducted with 190 HIV-positive men, and found that 6.3% them had detectable HPV in their oral fluid samples23. On the other hand, a study conducted in theUnited States and Spain with 166 patients showed a prevalence of 21% of oral HPV in HIV-positive MSM individuals, of which 11.1% were low-risk types and 66.6% were high-risk types24. In our study, oral HPV infection was detected in 3.5% of HIV-positive patients, in accordance withboth previous results and with the variability found in the prevalence of oral HPV in several studies9.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, a study was conducted with 190 HIV-positive men, and found that 6.3% them had detectable HPV in their oral fluid samples23. On the other hand, a study conducted in theUnited States and Spain with 166 patients showed a prevalence of 21% of oral HPV in HIV-positive MSM individuals, of which 11.1% were low-risk types and 66.6% were high-risk types24. In our study, oral HPV infection was detected in 3.5% of HIV-positive patients, in accordance withboth previous results and with the variability found in the prevalence of oral HPV in several studies9.…”
Section: Discussionmentioning
confidence: 99%
“…Although the known association with oncogenic human papillomavirus (HPV) with oropharyngeal HNSCC has led some to speculate viral co-infection as an explanation for the increased risk of HNSCC in HIV-positive populations, preliminary data from HNSCC specimens of these patients have not clearly supported this hypothesis [36]. Concerns of using systemic therapies for this population include risks of immunosuppression and increased toxicity; however, limited evidence suggests that appropriately selected patients can tolerate organ-preserving therapy [37,38].…”
Section: Patients Infected With Hivmentioning
confidence: 99%
“…2). These primers amplify DNA fragments in the L1 region encoding the hypervariable V loop of the major capsid protein generating a fragment size approximately 450 and 150 bp (McLemore et al 2010). Several types of PCR-based detection for HPV have evolved over the past decade.…”
Section: Hpv Biologymentioning
confidence: 99%